Prevention of the color changes in waterborne antimicrobial coatings with nano-functionalized siliceous filler - Barberia Roque, Leyanet (2020)
Color fastness represents the capacity of a given paint to maintain its original color over the timewhen exposed to biotic and abiotic environmental factors. The aim of this work is to assess the colorchanges due to the addition of Ag nanoparticles in a natural siliceous based material in coatings.Analysis of the color data from 24 hours showed the effectiveness of the functionalized materials todecrease the color change. Paints with nanoparticles added directly presented color variation rated asvery big, considering the colorimeter method by Teichmann, while with the addition of functionalizedsilica was barely evident. These results kept during the six months in which the study was conducted.